The Relationship between E-Commerce Consumer Privacy and Trust on Online Transactions - achmad zulfiqo irwan; ra afera ratna wijayanti (IULI Publisher, 2023)
ABSTRACT. The background of this research was that privacy and trust in online transactions are essential for the success of transactions. Recent studies suggest that many people either decline to provide their personal information over the internet or simply provide false information because most of them do not trust the protection of privacy. Privacy and Trust in the online transaction have to be fulfilled by the E-commerce website and relate to the consumer’s behavioral intention to the E-commerce website. The objective(s) of this research was to understand the relationship between privacy with trust and trust with behavioral intention and also to see the differences in Ecommerce consumer trust through sex, age, and website experience level. The hypothesis test uses correlation analysis on the relationship between privacy with trust and trust with behavioral intention. ANOVA test was also used in this thesis to find out trust differences through sex, age, and website experience level. The result of this research concludes that there is a positive relationship between privacy with trust and trust with the behavioral intention of E-commerce consumers. Also that there is a trust difference through sex but there are no trust differences between age andwebsite experience level.Keywords : Privacy, Trust, E-Commerce, Website